Anthocyanin Content and Antioxidant Activity of Red Chrysanthemum (Chrysanthemum morifolium Ramat.) at Different Flower Ages: Anthocyanin content and antioxidant activity of red chrysanthemum - ANISA MAGFIROH; ENDAH DWI HASTUTI; YULITA NURCHAYATI; NINTYA SETIARI (Borneo Journal of Resource Science and Technology, 2023)
Chrysanthemum sp. is a floricultural plant of the Asteraceae family with high economic value. The anthocyanin pigment in red chrysanthemum acts as an antioxidant, the content of which can be influenced by genetic factors such as the physiological age of the flower. This study aimed to determine the effect of flower age on anthocyanin content and antioxidant activity in red chrysanthemum plants. The age of red chrysanthemum used was 115 Days After Planting (DAP) (early bloom stage), 120 DAP (half-bloom stage), 125 DAP (blooming stage), and 134 DAP (wilted flower). The anthocyanin content was analysed using spectrophotometric methods. Antioxidant activity was determined by the DPPH method and then the absorbance was measured using a UV-Vis spectrophotometer. The results showed that the highest anthocyanin content was obtained at the age of 134 DAP at 3.56 mg/g, followed by the age of 115 DAP at 2.40 mg/g, then at 125 DAP at 1.95 mg/g and the lowest at 120 DAP at 1, 69 mg/g. The highest antioxidant activity was shown in chrysanthemum flowers aged 115 DAP which had an IC50 value of 288.85 g/ml. The research shows that wilted chrysanthemum flowers still contain anthocyanins so it can be used in various industrial fields such as chrysanthemum tea and additives for soap.